C-Reactive Protein and Cytokines in Polytrauma - E. K Gumanenko; N. S Nemchenko; V. V. Boyarintsev; S. V. Gavrilin; D. A. Vologzhanin; A. A. Rud (Общая реаниматология, 2007)
Objective: to study the association of C-reactive protein (CRP) with cytokines in polytrauma.Subjects and methods. Eighty-four victims with severe concomitant injury were examined. Twenty-five (29.7%) patients developed sepsis, death being observed in 83.3%. CRP was daily determined in the sera of the victims, by using CRP latex test kits (HUMATEX, Germany). On days 1, 3, 7, 10, and 15 after injury, serum and lymphocytic culture IL-2, IL-4, TNF-a, IFN-y, and HLA-DR were studied on an automatic Elx 800 Universal Microplate Reader enzyme immunoassay analyzer (BIO-TEK INSTRUMENTS, Inc., USA), by applying enzyme immunoassay systems (OOO «Cytokine», Saint Petersburg, Russia).Results. No complications were observed with a CRP level of 40 mg/l on day 1 and its further reduction. The CRP level of 40 mg/l on day 1 (without use of glucocorticoids) and its prolonged increase were determined in visceral inflammatory and infectious complications. The CRP level of 120 mg/l within the first 7 days was noted in subsequently developed sepsis. Glucocorticoids and specific immune drugs resulted in a reduction or complete disappearance of CRP. When the latter were discontinued, CRP appeared in the quantity reflecting the effect of treatment. In the absence of multiple organ dysfunctions, the level of CRP decreased as the infectious process diminished. The low level of CRP and the activation of an infectious process suggest the areactivity of an organism. With the CRP level of 40 mg/l, the spontaneous production and level of blood IL-4 increased less significantly, whereas those of IFN-y rose more substantially; the induced activity of TNF-a also more drastically decreased (by 10 times versus 2.2) with a CRP level of 40 mg/l. Irrespective of the level of CRP, the induced activity of IL-4 decreased by 59%, suggesting immunosuppression. There was no association of CRP with IL-2 and HLA-DR.Conclusion. Daily blood CRP analysis in injury makes it possible to predict visceral inflammatory infectious complications and sepsis. CRP inhibition of the anti-inflammatory properties of IL-4 causes an uncontrolled systemic inflammatory response. The pattern of relationships of IL-4, TNF-a, IFN-y, and CRP should be borne in mind when posttraumatic sepsis is treated.